Perancangan meja dan kursi bar multifungsi untuk ruang keluarga milenial di ruang hunian terbatas - Kusuma, Gabrielle Mahanaim; Andrianto, Andrianto; Adiluhung, Hardy (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2025)
The increase in population in Indonesia has resulted in a reduction in the availability of residential land. This made an impact such as residential space becoming smaller. Even though space is limited, millennial families still need to do lots of activities because of their tendency to do several jobs at once. In dealing with these problems, Open Plan concept is generally used. One application of the Open Plan concept is the use of bar tables in exchange to dining tables because their relatively small size and multifunctional. There isn’t much research on bar tables other than for cooking. Apart from that, bar tables and barstools on the market have the potential to be improved to suit millennial families’ needs better. Thus, through this research it is hoped that we’ll be able to design a bar table and barstool that has more functions, like for interacting with family, implementing Work from Home (WFH), additional cooking areas, and optimizing space limitations. The method used in this research is a qualitative research method and User Centered Design design method. The result of this design is a bar table that uses a lift-up system, features sockets and shelves, also barstools with foldable seat backs.